The Utility of Ambulatory pH Monitoring in Patients Presenting with Chronic Cough and Asthma - KF AlHabib; S Vedal; P Champion; JM FitzGerald (Canadian Journal of Gastroenterology)
OBJECTIVE: To evaluate the prevalence of gastroesophageal reflux disease (GERD) in patients presenting with asthma and chronic cough.